Mechanical Properties of Sugarcane Bagasse Fiber Composites: Epoxy vs Polyester Resin Matrices - Prasetya, Bayu; Solafide Sipahutar, Wahyu; Andryan Prakoso, Ahmad; Fitri, Anisa (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2025)
This study aims to evaluate the mechanical properties of sugarcane bagasse bagasse fiber-reinforced composites using two types of matrix resins (i.e epoxy and polyester). The composites were fabricated using the hand lay-up method, with sugarcane bagasse bagasse fibers serving as the natural reinforcement. The tests conducted included visual fracture analysis, tensile testing, and flexural testing. The results showed that the epoxy-based composite achieved a tensile strength of 26.43 MPa, slightly higher than the polyester-based composite at 26.06 MPa. In the flexural test, the epoxy matrix composite exhibited a flexural strength of 89.53 MPa, significantly higher than the polyester matrix at 49.12 MPa. These findings indicate that the type of matrix resin has a significant influence on the mechanical performance of natural fiber composites, particularly in applications requiring high flexural strength.